PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY BERBANTUAN PUZZLE PICTURE TERHADAP HASIL BELAJAR IPA SISWA - Septi Karuniawati; Slamet Utomo; Gunawan Setiadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the effect of the guided inquiry learning model with a puzzle picture on the fifth-grade elementary school students’ learning outcomes on the material of human respiratory organs. The research described in this article is quantitative research with an experimental method. The research population involved fifth-grade elementary school students of Segugus Jenderal Sudirman in Pulokulon. The sample in the research was the fifth-grade students of SDN 4 Karangharjo as an experimental class by applying a guided inquiry model assisted by a puzzle picture and fifth-grade students of SDN Kecil Karangharjo as a control class by applying a conventional model. The sampling technique used purposive sampling. Data collection techniques were carried out through tests, observations, and documentation. Data analyses were prerequisite analysis tests (normality and homogeneity tests) and hypothesis testing with t-test and Normalized Gain (N-Gain). The results showed that there was an effect of the guided inquiry learning model assisted by a puzzle picture on students’ learning outcomes with the results of tcount of 6.154, ttable of 2.0277. Thus, tcount was higher than ttable.